Influência dos parâmetros de laminação a quente e tratamentos térmicos sobre a formação de estrutura perlítica heterogênea em aço ABNT 1045 para hastes amortecedores - Ricardo Correa Botelho (2004)
The production of a steel for the automobile industry demands a high control level of its mechanical properties. The front strut, which is an important component responsible for the car safety, goes through severe inspections in order to avoid that any existing abnormality reaches the final component. Belgos plant, located in João Monlevade city, is developing a wire rod rolling process for the 22.5mm diameter in order to attend this market. The front strut, which is produced using the steel ABNT1045, needs to have a very low variability of its mechanical properties since it is a steel with a high technological responsibility. A strict control of the reheating and rolling processes gives a homogenous austenitic structure that is mandatory to produce a homogeneous final structure. This study evaluates the effect of the rooling mill parameters on the grain size variability in order to have a wire rod that attends the necessities of the front strut customers. The evaluation of the changes in the billet reheating temperature and in the cooling speed of the wire rod is the methodology applied to fully understand the effects of these process parameters on the heterogeneous structure formation.